Null arguments: the case of Japanese and Romance - Zushi, Mihoko (Lingua, 2003)
The first half of this article presents an overview of theoretical and empirical issues raised by the phenomena of argument drop within the principles-and-parameters approach, with special attention to the comparison of the argument drop in Japanese and the Romance languages. The latter half of the article is devoted to reconsidering the two parameters dealing with argument drop that have been proposed in the literature, namely, the pro-drop parameter and the zero-topic parameter. This article attempts to eliminate the need for postulating the two parameters as independent parameters and derive the presence or absence of null arguments from a particular property of T, in accordance with the view that all parameters are morphological in nature. It is argued that the occurrence of null subjects in finite clauses is a consequence of the lexical, rather than functional, nature of T, which holds true in Japanese and Italian, but not in English. It is also argued that the presence of zero topics that plays a crucial role in identifying null arguments is allowed when they are licensed by a predication relation, and that such a predication relation can be made available by the predicative nature of the projection of T in Japanese, but cannot by the argument nature of the projection of T in Italian and English.